Two new species of genus Joruma McAtee (Hemiptera: Cicadellidae: Typhlocybinae) from Viçosa, Minas Gerais State, Brazil - Coelho, Luci Boa Nova; Da-Silva, Elidiomar Ribeiro; Ferreira, Paulo Sérgio Fiuza (Zootaxa, 2016)
Joruma abernardesi sp.nov. and Joruma phrolfsi sp.nov. (Typhlocybinae: Jorumini) are described based on specimens from Mata do Paraíso, an Atlantic Forest reserve located at Viçosa municipality. This is the first record of the genus Joruma McAtee in Minas Gerais State, southeastern Brazil.